Deconstructing gender norms in pesantren: a critical etnographic study of the pesantren curriculum in Indonesia - Ach Barocky Zaimina; Asnawan Asnawan; Anuwat Sohwang (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2025)
Pesantren in Indonesia maintain traditional gender structures through formal and non-formal curricula, reproducing male dominance, limiting female participation, and reinforcing patriarchal hierarchies amid rapid social change. This study aims to analyze the dynamics of gender power reproduction and contestation in three pesantren in East Java through a critical ethnographic approach, tracing layered patriarchy and symbolic agency within pedagogical practices and the pesantren curriculum. This study employed a critical ethnographic approach with a case study design. Data were collected through semi-structured interviews with 10 informants and analyses of curriculum documents. Data analysis applied Carspecken’s critical ethnographic framework, supported by source triangulation, theoretical triangulation, and ideological critique. The findings revealed four main issues: (1) pesantren curricula reproduce gender inequality through patriarchal roles and vertical power relations; (2) resistance emerges through progressive female teachers, critical students, and informal learning groups; (3) gender-responsive curricula are hindered by monolithic religious content, patriarchal structures, and limited teacher competence; and (4) minimal representation of female Islamic scholars limits students’ recognition of women as religious role models. The study demonstrates that pesantren reproduce patriarchy through curricula, institutional structures, and symbolic representations, while resistance from female teachers and students remains largely symbolic due to the absence of sustainable structural reform. This study contributes to expanding the concept of patriarchal habitus and proposes a pesantren patriarchy contestation model through curriculum reform, critical pedagogy, inclusive policies, and strengthening women’s participation toward sustainable structural transformation.